Disruptive neoclassical tearing mode seeding in DIII-D with implications for ITER. (1st May 2022) - La Haye, R.J.; Chrystal, C.; Strait, E.J.; Callen, J.D.; Hegna, C.C.; Howell, E.C.; Okabayashi, M.; Wilcox, R.S.
Abstract: New studies identify the critical parameters and physics governing disruptive neoclassical tearing mode (NTM) onset. An m / n = 2/1 mode in DIII-D that begins to grow robustly after a seeding event (edge localized mode ELM or sawtooth precursor and crash) causes the mode rotation to drop close to the plasma's E r = 0 rest frame; this condition opens the stabilizing ion-polarization current 'gate' and destabilizes an otherwise marginally stable NTM. Our new experimental and theoretical insights and novel toroidal theory-based modeling are benchmarked and scalable to ITER and other future experiments. The nominal ITER rotation at q = 2 is found to be stabilizing ('gate closed') except for MHD-induced transients that could 'open the gate'. Extrapolating from the DIII-D ITER baseline scenario (IBS) discharges, MHD transients are much more likely to destabilize problematic robustly growing 2/1 NTMs in ITER; this makes predictions of seeding and control of both ELMs and sawteeth imperative for more than just minimizing divertor pulsed-heat loading.